EXPLORING BILIARY ILEUS: A RARE AND COMPLEX CLINICAL CASE - Kasalović, Mladen (Acta medicae Medianae, 2026)
Biliary ileus is a rare complication associated with cholelithiasis. Although it accounts for less than 4% of small bowel obstructions in patients under 65 years of age, its prevalence rises to 25% in patients over 65 years of age. Physicians are faced with the decision of whether to opt for immediate closure of a single- or two-stage cholecystoenteric fistula or to wait for natural closure. A 62-year-old female patient presented to the surgical clinic with severe abdominal pain, predominantly on the right side, and a sensation of bloating. She reported symptoms of constipation, nausea, and vomiting. An emergency exploratory laparotomy was scheduled. During the surgical procedure, careful exploration revealed significant dilation of the proximal part of the intestine, and a gallstone was found in the jejunum. The gallstone was successfully removed, followed by closure of the enterotomy site. This report highlights a condition that is rarely seen in practice. In older patients presenting with clinical manifestations of bowel obstruction and chronic issues with the gallbladder, this rare disease should be considered, particularly in women and elderly patients.